Lipid metabolism and the endoplasmic reticulum - Agellon, Luis (Henry Stewart Talks, 2007)
Biological roles of lipids, Major lipid classes found in the cell, Metabolism of lipids in the ER, Examples of lipidmetabolizing enzymes found in the ER, Strategies for maintaining cellular cholesterol homeostasis, Activation of gene expression by SREBPs, Situations that cause ER stress, The unfolded protein response (UPR) and lipid metabolism